A zwitterionic triphosphenium compound as a tunable multifunctional donor. Issue 14 (8th December 2015) - Kosnik, Stephanie C.; Macdonald, Charles L. B.
Abstract : We present a zwitterionic triphosphenium molecule which features dicoordinate, tricoordinate and tetracoordinate phosphorus centers in addition to a cyclopentadienyl moiety. Crystallographic, computational, electrochemical and spectroscopic data illustrate and rationalize the reactivity of this molecule as a multifunctional ligand for both transition metals and main group acceptors and suggest how the donor properties may be tuned. Abstract : The preparation of a novel triphosphenium zwitterion featuring di-, tri-, and tetra-coordinate phosphorus centres derived from a 1, 2, 4-tris-(diphenylphoshinyl)cyclopentadienyl framework is described. The reactivity of this potentially multidentate donor with protons, elemental sulfur and gold(i ) chloride is examined, and the preferential reactivity of the pendant phosphine group over the P(i ) centre is rationalized on the basis of density functional theory investigations.